Animal Models of Prefrontal-Executive Function. - Chudasama, Yogita (Behavioral Neuroscience, 2011)
The writer reviews the literature on animal models used for investigating specific structure-function relationships within the prefrontal cortex, particularly as they relate to complex executive behaviors. The writer describes a broad range of experiments, conducted in rats and monkeys, that involve the targeted disruption of neural circuits combined with behavioral testing using carefully designed cognitive paradigms. The writer discusses what this body of research reveals about the distinct contributions of dorsal, medial, and ventral prefrontal cortex to different aspects of executive function.